2018
DOI: 10.7882/az.2018.019
|View full text |Cite
|
Sign up to set email alerts
|

Town roo, country roo: a comparison of behaviour in eastern grey kangaroos Macropus giganteus in developed and natural landscapes

Abstract: Many species have adapted their behaviour to survive in anthropogenically developed environments (hereafter referred to as developed). Eastern grey kangaroos Macropus giganteus are common in developed areas, however very few studies have evaluated their behavioural adaptations to developed landscapes. This study compared the behaviour of eastern grey kangaroos in a developed environment to those surrounded by a natural environment. Data were collected using infra-red camera traps that recorded one minute video… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Prior to this study, the effects of urbanization on eastern grey kangaroos vigilance has only been investigated once, when comparing two populations that were found in close proximity to each other [28]. The results from our study concur with the former study, which observed a higher time being spent vigilant at the developed site as compared to the natural.…”
Section: Discussionsupporting
confidence: 86%
“…Prior to this study, the effects of urbanization on eastern grey kangaroos vigilance has only been investigated once, when comparing two populations that were found in close proximity to each other [28]. The results from our study concur with the former study, which observed a higher time being spent vigilant at the developed site as compared to the natural.…”
Section: Discussionsupporting
confidence: 86%
“…Research was conducted at Yarramundi Paddocks (33°36′47.85″S/150°43′47.429″E), Western Sydney University’s (WSU) Hawkesbury campus as described previously [ 15 , 19 21 ].…”
Section: Main Textmentioning
confidence: 99%
“…Unfortunately, the kangaroos at the study site had a very large flight distance and were extremely difficult to capture to obtain blood samples, hence tissue samples were obtained opportunistically from road-killed kangaroos, which proved to be a more effective and non-invasive method of collecting samples for DNA extraction. The population density of kangaroos inhabiting the site was previously estimated as 4.6 kangaroos/ha [ 21 ], hence 1416 kangaroos were estimated to be utilizing the site. Based on the estimated population size at the site, this sample size accounts for less than 2% of the population, hence as this is a small sample of the larger population the high level of relatedness between individuals was not expected.…”
Section: Limitationsmentioning
confidence: 99%
“…2018b), although this may have been influenced by the short tracking duration (≤2 months). Green‐Barber and Old (2018) reported larger ranges (˜170 ha) for two males tracked for almost two years in Richmond NSW.…”
Section: Advances In the Knowledge Of Peri‐urban Kangaroo Populationsmentioning
confidence: 99%
“…There is also some evidence of kangaroos adapting to the peri‐urban environment by modifying their activity patterns. Kangaroos became active earlier in the morning at a peri‐urban site than at a more natural site (Green‐Barber & Old, 2018), but data from additional sites are needed to confirm a general adaptive response.…”
Section: Advances In the Knowledge Of Peri‐urban Kangaroo Populationsmentioning
confidence: 99%